A rare complication of amiodarone: Diffuse alveolar hemorrhage [Amiodaron'a baǧli ender bir komplikasyon: Yaygin alveolar hemoraji] - (:unkn) unknown (Turkish Anaesthesiology and Intensive Care Society, 2014)
Amiodarone, a frequently used antiarrhythmic drug is known for having neurological, ophthalmic, cutaneous, hepatic and pulmonary side effects. Signs of pulmonary toxicity are observed dependent on the duration of exposure and the dose administered. Pulmonary complications occur in 10-17% patients and interstitial pneumonia is the most common one. In this case report we present a female patient with acute atrial fibrillation associated with rapid ventricular response treated with amiodarone who developed diffuse alveolar hemorrhage, a rare complication of amiodarone.
Keywords: Amiodarone; Atrial fibrillation; Diffuse alveolar hemorrhage